The Role of Cathelicidin in Dermatology Skin - Apriani, Diana Kurnia; Dwiyana, Reiva Farah; Chaerunisaa, Anis Yohana (Jurnal Sains dan Kesehatan, 2024)
Acne, Atopic Dermatitis, Psoriasis and Rosacea are examples of chronic inflammatory skin conditions. One characteristic of many skin disorders is the dysregulation of innate immunity in the skin. Acne, Atopic Dermatitis, Psoriasis, and Rosacea all have problems with the expression, function, or processing of the key innate immune effector molecule in the skin, cathelicidin LL-37. Cathelicidin induction can be altered to treat Acne and Atopic Dermatitis, which lessens the efficiency of the antimicrobial barrier. However, cathelicidin is overexpressed in Psoriasis and Rosacea. The most recent research on cathelicidin LL-37’s involvement in the etiology of inflammatory skin disorders will be included in this review. Since cathelicidin LL-37 may one day be employed as a therapeutic target, many cutting-edge therapy methods for the disease will be discussed. Keywords:          Antimicrobial Peptide, Cathelicidin, Dermatology Skin